Phenotypic rescue of a Drosophila model of mitochondrial ANT1 disease - Suvi Vartiainen; Shanjun Chen; Jack George; Tea Tuomela; Kaisa R. Luoto; Kevin M. C. O'Dell; Howard T. Jacobs (The Company of Biologists, 2014)
A point mutation in the Drosophila gene that codes for the major adult isoform of adenine nuclear translocase (ANT) represents a model for human diseases that are associated with ANT insufficiency [stress-sensitive B1 (sesB1)]. We characterized the organismal, bioenergetic and molecular phenotype of sesB1 flies then tested strategies to compensate the mutant phenotype. In addition to developmental delay and mechanical-stress-induced seizures, sesB1 flies have an impaired response to sound, defective male courtship, female sterility and curtailed lifespan. These phenotypes, excluding the latter two, are shared with the mitoribosomal protein S12 mutant, tko25t. Mitochondria from sesB1 adults showed a decreased respiratory control ratio and downregulation of cytochrome oxidase. sesB1 adults exhibited ATP depletion, lactate accumulation and changes in gene expression that were consistent with a metabolic shift towards glycolysis, characterized by activation of lactate dehydrogenase and anaplerotic pathways. Females also showed downregulation of many genes that are required for oogenesis, and their eggs, although fertilized, failed to develop to the larval stages. The sesB1 phenotypes of developmental delay and mechanical-stress-induced seizures were alleviated by an altered mitochondrial DNA background. Female sterility was substantially rescued by somatic expression of alternative oxidase (AOX) from the sea squirt Ciona intestinalis, whereas AOX did not alleviate developmental delay. Our findings illustrate the potential of different therapeutic strategies for ANT-linked diseases, based on alleviating metabolic stress.